Sediment elemental composition (XRF) of sediment core GeoB19904-2, measured with 30 kV - Jens Weiser (PANGAEA, 2025)
XRF Core Scanner data of sediment core GeoB19904-2 from Labrador Sea were collected every centimetre downcore over an active area of 15 mm^2 with a downcore slit size of 10 mm using generator settings of 30 kV directly at the split core surface of the archive half with XRF Core Scanner II (AVAATECH Serial No. 2) at MARUM, Bremen.
In: Weiser, J (2025): Sediment elemental composition (XRF) of sediment core GeoB19904-2 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.984271